The potential of endophytic bacteria isolated from atung fruit seeds as antibacterial against skin pathogens - Melda Yunita; Adelia Mantong; Halidah Rahawarin (JPBIO (Jurnal Pendidikan Biologi), 2023)
Antibiotic resistance is one of the biggest threats to global health today. Estimated by 2050, antibiotic resistance will cause around 10 million deaths per year if alternative treatments have not been identified. This study was aimed to determine the potential of endophytic bacterial isolates from the seeds of atung fruit (Parinarium glaberrimum Hassk) as an antibacterial against skin pathogens Cutibacterium acnes and MDR Staphylococcus aureus, and Staphylococcus epidermidis. This research was a descriptive observational research with laboratory experimental methods. This study used isolates of endophytic bacteria isolated from the seeds of atung fruit which were tested with pathogenic bacteria. The results showed that 2 of 7 endophytic bacterial isolates were able to inhibit the growth of C. acnes with clear zone diameter of 4 mm and 9 mm, respectively, yet couldn’t able to inhibit MDR S. aureus and S. epidermidis. This study concluded that the 2 isolates (isolate BBA5 and BBA9) could have potential as antibacterial against C. acnes. While 5 other isolates had not been able to inhibit the whole pathogenic bacteria tested. An optimization is necessary in an effort to develop these isolates as antibacterial.